Obtainment of intergeneric rootstocks in citrus - Ramos, José Darlan; Pasqual, Moacir; Ribeiro, Valtemir Gonçalves; Antunes, Luís Eduardo Corrêa (Pesquisa Agropecuaria Brasileira, 1997)
Inbreds Poncirus trifoliata (L.) Raf x Rangpur limes (Citrus limonia Osbeck) from the orchard of Universidade Federal de Lavras, MG, Brazil, were obtained as rootstocks for pest and disease resistance. Studies comparing male and female progenitors with their inbreds were carried out: fruits harvested were measured, seed numbers were taken, and polyembryony index was determined by excising the embryos at several development stages and inoculating them in vitro. The trifoliate trend of male progenitor ('Trifoliata' lemon) kept the dominance over the normal female progenitor ('Cravo' lemon). No progenitor dominance for seed total number, viable seeds number, and fruit diameter was observed. Fruit polyembryony index obtained throught artificial pollination (2.39 embryos/seed) were maintained in inbred progenies (1.21 embryo/seed), indicating that such traits are able to be characterized as monoembryonics, although they were similar to the female progenitor which showed 1.41 embryo/seed.